Colonização bacteriana na região marginal de restaurações cerâmicas: efeito do método de remoção do cimento e do polimento - Pereira, Sarina Maciel Braga [UNESP] (2015)
Abstract This study evaluated the effects of excess cement removal techniques, with or without posterior polishing, on the biofilm formation and micromorphology in the marginal region of the tooth/restoration. From bovine teeth, 96 dentin blocks (4 x 8 x 2 mm) were produced, molded and reproduced in type IV gypsum, on which 96 pressed ceramic blocks (Vita PM9 4 mm x 8 mm x 2 mm, Vita Zahnfabrik) were produces via lost wax technique. The dentin blocks and their respective ceramic blocks were cemented with a self-adhesive resin-cement (RelyX U200, 3M ESPE) and cement excess was removed using different techniques, followed by polishing with silicone tips or, in some cases, not polished at all: MBr: microbrush and photoactivation, MBr-Pol: MBr + polishing, Pi: brush and photoactivation, Pi-Pol: PI + polishing, Photo-Expl: 5 s initial photoactivation, explorer and final curing, Photo-Expl-Pol: Photo-Expl + polishing, Photo-Bi: 5 s initial photoactivation, scalpel and final curing, Photo-Bi-Pol: Photo-Bi + polishing. After 24 hours, the samples marginal region roughness was analyzed using a profilometer (Mitutoyo SJ-400 Tokyo, Japan; three measurements on each sample). Micromorphological analyses of the region were performed by stereoscopic microscope and SEM. Then the samples were contaminated with sucrose broth standardized suspension with Streptococcus mutans, Staphylococcus aureus and Candida albicans and incubated for a period of 48 hours. The samples were quantitatively analyzed for bacterial adherence in the marginal region by confocal laser scanning microscopy and counting of colony forming units (CFU/ml), and qualitatively analyzed using SEM. Roughness data (Ra) were submitted to 2-way ANOVA, Tukey test (5%) and Student's-t tests. CFU, Biomass and bio thickness data were analyzed by Kruskal Wallis', Mann-Whitney's e Dunn's tests. The removing technique statistically influenced the roughness (Ra; p ˂ 0.05), when comparing polished and unpolished...